Evaluating pile foundation design due to groundwater level lowering - Vo Ai Mi Nguyen; Hoang Le; Thi Anh Hong Le; Huu Truong Nguyen (CTU Journal of Innovation and Sustainable Development)
In Viet Nam, ground subsidence has been occurring at an alarming rate, raising concerns for pile foundation design. This issue is primarily caused by excessive groundwater extraction for water supply, irrigation, aquaculture, and other uses. Thus, in this study, the evaluation of pile capacity due to groundwater level (GWL) lowering as a preliminary guideline for structures is proposed. This study analyzed different cases of GWL lowering from 0 m to 2 m, and pile size varied from 18 x 18 cm to 45 x 45 cm, to evaluate the allowable bearing capacities for single piles and pile groups. The results indicated that when lowering the GWL from 0 to 2 m, the allowed bearing capacity varied by 5.75–174.70 tons for single piles and 11.95–808.18 tons for pile groups. Besides, when the pile size increased, the bearing capacity increased in the range of 6.38–41.46 tons (size 18 x 18 cm) to 16.30–174.70 tons (size 45 x 45 cm) for a single pile and 11.95–191.81 tons (size 18 x 18 cm) to 33.49–808.18 tons (size 45 x 45 cm).  The result of this study underscores the significance of predicting the bearing capacity of pile foundations due to the variation in groundwater level.